BUDDENBROOKS AT THE BLACK SEA. VLADIMIR JABOTINSKYS ODESSA-NOVEL THE FIVE - von der Lühe, Irmela (Porównania, 2019)
Irmela von der Lühe, BUDDENBROOKS AT THE BLACK SEA. VLADIMIR JABOTINSKYS ODESSA-NOVEL THE FIVE. “PORÓWNANIA” 1 (24), 2019. Vol. XXIV, P. 123-133. ISSN 1733-165X. When Jabotinksys novel first appeared in Germany (2012) it was celebrated as a spectacular literary event. Jobtinsky’s Jewish family novel is situated in the decades before the revolution of 1905; it deals with revolutionary hope and disappointment, with Jewish assimiliation and the idea of a new liberal and tolerant world. It ends with a complete decline of these visions into brutal antimodernism. This article describes special narrative strategies in producing spaces of memory as streets, places and special public locations. Thereby political events appear as analogies to theater plays and also in a symbolistic framework. By this Jabotinskys novel has become a controversial space of memory not only for political but also literary reasons.